Translation and validation of adult carer quality of life (ac-qol) questionnaire and mediation analysis of depression, anxiety and stress on quality of life of informal caregivers of stroke survivors in Kelantan - Khan, Erwan Ershad Ahmad (2024)
Introduction: As the global population ages and the prevalence of chronic illnesses rises, the demand for caregivers has grown substantially, prompting increased interest in understanding caregivers' quality of life (QoL). Caring for stroke survivors presents unique challenges and rewards, impacting caregivers' QoL. Objectives: To determine the characteristics of publications on caregivers' QoL through bibliometric analysis, to translate and validate the Malay version of the Adult Carer Quality of Life Questionnaire (AC-QoL), to model relationships between informal caregivers’ and stroke survivors’ factors with informal caregivers’ QoL and to estimate the mediation effects of depression, anxiety, and stress. Materials and Methods: Bibliographic data were extracted from the Scopus database using terms like “caregivers” and “quality of life”. The analysis included original articles or reviews in English up to August 2023, utilizing the 'bibliometrix' package in RStudio. The second study was a cross-sectional study that translated the AC-QoL into Malay through a ten-step process. Content and face validation were conducted with six experts and ten subjects, respectively. Confirmatory factor analysis (CFA) was performed on data from 222 informal caregivers. 60 informal caregivers were subjected for retesting for stability. The third study, another cross-sectional study, analysed data from 250 informal caregivers. Linear regression modelled relationships between stroke survivors’ and informal caregivers’ factors with informal caregivers’ QoL. Hayes's PROCESS macro model 4 for bootstrapping indirect effects was used to estimate the mediation effects of depression, anxiety, and stress Results: Since 1989, 1859 original research articles and reviews were published, with a 15.52% annual growth rate. The USA led with the most publications (327), citations (9993), and collaboration activity. Key keywords included “depression”, “anxiety”, “stroke”, “dementia”, “cancer”, and “burden”. Clusters for “depression”, “anxiety”, “cancer”, and “family caregivers” dominated current research, while “dementia” and “Alzheimer's disease” are emerging topics. In the second study, content validity indicated rephrasing for two items. Face validity was high for all items. CFA suggested removing four items due to low factor loading, resulting in a model with satisfactory indices: CFI (0.889), TLI (0.877), RMSEA (0.066), and SRMR (0.064). Composite reliability ranged from 0.77 to 0.91. Significant differences were observed in QoL scores among informal caregivers with varying levels of depression, anxiety, and stress. The questionnaire showed good stability (ICC = 0.86). In the third study, stroke survivors’ dependency (b = 0.14), informal caregivers’ depression (b = -0.81), and anxiety (b = -0.73) were significantly associated with informal caregivers’ QoL. Depression (effect = 0.02) and anxiety (effect = 0.01) partially mediated the relationship between stroke survivors’ dependency and informal caregivers’ QoL. Conclusion: Informal caregivers' QoL is profoundly influenced by the demands of caregiving, particularly for stroke survivors. The bibliometric analysis highlights the evolving research landscape, while the validation of the AC-QoL provides a reliable tool for assessing informal caregivers' QoL in Malaysia. The mediation analysis underscores the significant role of psychological distress, specifically depression and anxiety, in modulating the impact of stroke survivors’ dependency on informal caregivers' QoL. These insights emphasize the necessity for targeted screening and interventions to alleviate informal caregivers' psychological burdens, ultimately enhancing their quality of life.